Students’ Perception towards Storytelling in Developing Speaking Skills at English Department of Mulawarman University - Karomah Khairunnisa; Weningtyas Parama Iswari; Yuni Utami Asih (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2021)
The study aimed to know the students’ perception, challenges, and how to overcome the challenges of storytelling in the development of their speaking skills. This study was conducted at English Department Mulawarman University. The design of this study was mixed-method study with the purpose to illustrate students’ perception of the use of storytelling in speaking class. There were 46 third-semester students in the academic year 2019/2020. The instruments were questionnaire and interview guidelines. The data from the questionnaire were used to select students to be interviewed. Six students were selected as the interviewees, they had high, moderate and low level of perception towards the use of storytelling in speaking class. Afterward, the researcher collected the interview data and triangulated the data from the questionnaire and interview. The finding showed that students had a positive experience in using storytelling techniques in speaking class it showed by the result of the mean score of questionnaires was 3.83, especially in developing their components of speaking skills. The students also stated that in using the storytelling techniques they found the effectiveness of storytelling in their speaking development. The study also found that the students’ challenges were fear of mistake, anxiety, shyness, and lack of confidence. The students overcame their challenges through relaxation, preparation, peer seeking, and positive thinking. The researcher suggests that teachers and lecturers do storytelling more often in the class to improve their speaking skills, and to overcome student challenges the teachers or lectures can also give students time to prepare and create a relaxed atmosphere before doing storytelling.